Entrepreneurship education scholarly progress and future challenges - Hägg, Gustav 1983-; Kurczewska, Agnieszka 1980- (New York, NY Routledge, 2022)
"The discussion around whether entrepreneurship can be taught is becoming obsolete as the number of entrepreneurship courses, specializations and degrees is rising at an unprecedented rate all over the world and the demand for entrepreneurial education teachers or instructors is constantly growing. The global community of entrepreneurial education proponents is enthusiastic about the possibility of spreading the idea of entrepreneurship, as it is believed to benefit societies and economies in addition to influencing human development on an individual level. The fervour is nurtured by public policies and the development of an enterprising culture in the public discourse. In this discourse, entrepreneurship is treated as a panacea for numerous social and economic problems. This book is a solid reference point for all who are interested in conducting research on entrepreneurial education or engaged in teaching entrepreneurship. It is a compendium of knowledge about entrepreneurial education as a research field, seen from the perspective of the last four decades, its complete contemporary history. It reviews the progress of the field from the outset to the present in terms of its socio-economic context, changes in the academic community, but also its research focus and methodological development. This uniquely comprehensive book is a resource of both knowledge on entrepreneurial education research and inspiration for future studies within the field. This timely and relevant book provides practical insights for educators when developing their teaching practice and will be of interest to entrepreneurship educators and entrepreneurship education researchers"--
Includes bibliographical references and index.
Keywords: Entrepreneurship; Entrepreneurship -- Study and teaching